Former à « prendre sa place » dans une équipe du travail social : une dimension collective des pratiques de tutorat - Dominique Trébert; Fanny Bovey; Camille Montefusco; Marianne Zogmal (Éducation et Socialisation)
In this contribution, we focus on practical training in the field of social work and on the collective dimension of training processes. We investigate how a student can take her place in the collective work context, and how the tutor and the members of a work team adjust to it. Through an analysis of verbal and non-verbal interactions, we seek to access detailed traces of the interactional modalities implemented in the practical training within a socio-educational institution. In the three excerpts analysed, we show that taking one's place in a team represents a permanent challenge for the learner, but also for the trainers within the professional team. More generally, the proposed reflection, which is based on an interactionist and video ethnographic perspective, illustrates the specificities of tutoring practices in social work.